Analisis Pengaruh Produksi Kakao Terhadap Pertumbuhan Ekonomi di Indonesia - Yolanda Desi Anggraini Silalahi; Roby Andika; Enjelina Damayanti; Novia Miftakhul Qisthi; Muhammad Akbar Husain; Nurlela Nurlela; Disya Ayu (CV. ALIM'SPUBLISHING, 2024)
This study looks at the relationship between Indonesian cocoa production and economic expansion. This study investigates the relationship between Indonesia's economic growth and cocoa production using quantitative methodology and secondary data. A 1% increase in cocoa production is associated with a 1% increase in economic growth, according to the findings of a simple linear regression study. Because other factors not included in the analysis also have an impact, the coefficient of determination () of 0.011 indicates that the impact of cocoa production on economic growth is around 1%. Additionally, hypothesis testing shows how independent factors work together to influence the dependent variable. The findings of this research contribute to the understanding of how cocoa production can influence economic growth in Indonesia and can be used as a consideration in developing more effective economic strategies.